A guide to conducting online research - Schreiner, Anthony E; Gaiser, Ted J (London: SAGE Publications, 2009)
This guide is designed to support students, academics and practitioner researchers in using technology as part of their research.
Bibliography.
Keywords: INTERNET SEARCHING; RESEARCH--METHODOLOGY; INTERNET RESEARCH; RESEARCH COLLABORATION